EFEKTIVITAS LAYANAN BIMBINGAN DAN KELOMPOK MENGGUNAKAN TEKNIK ROLE-PLAYING UNTUK MEREDUKSI PERILAKU AGRESIF PADA SISWA KELAS VIII DI SMP NEGERI 7 CIMAHI - Nindya Juniar Fatsyari; Ika Mustika; Dona Fitri Annisa (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This research is based on the existence of various cases motivated by aggressive behavior among adolescents. In this research, the use of group guidance services with role-playing techniques is one method of solving the problem. The use of mixed method research methods in this study became the achievement of the goal of reducing aggressive behavior indicated in a number of students. The results of the sample selection using random sampling obtained subjects totaling 15 students consisting of 11 male students and 4 female students in class VIII at SMP Negeri 7 Cimahi. Instruments used from observation sheets, interviews, and questionnaires.  In the pretest, the results obtained were 68.93%. While in the posttest results obtained results of 57.93%. the results of the calculation of the average value on the pretest and posttest showed that there was a decrease of (57.93% < 68.93%). . Can be reviewed from the average N-Gain Score (0.33). In addition, the obstacles experienced by teachers in handling efforts and student obstacles in carrying out activities. So it can be concluded that group guidance service activities with role playing techniques can reduce adolescent aggressive behavior in class VIII students at the Junior High School level.